ESPORTS-DASH : ESPORTS EVENT MANAGEMENT SYSTEM USING PROGRESSIVE WEB APPLICATIONS (PWA) - Ahmad Sufi, Abdul Hamid (Universiti Malaysia Sarawak (UNIMAS), 2019)
Electronic sports (Esports) gains worldwide attention and recognition as a genre of sports since recent decades. Esports event still at its early development has problems of its own. Managing esports event is different than traditional sports, hence, its own event management system created solely to handle the task. There are a number of esports event management system, both online and offline, which can be seen in the market. This diversity is welcomed, still, Esports-Dash system is a new approach of esports event management system harnessing the progressive web application (PWA). The system is answering the problems of managing event through traditional method such as log book and automating several activities through the use of PWA. This system caters to personal computer user and mobile phone user by web browser.